Pelaksanaan Layanan Bimbingan dan Konseling Bidang Pengembangan Karier Menuju Fase F di SMA Negeri 2 Palembayan - Sayddiyah, Halimahtun; Syukur, Yarmis; T, Taufik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Research in the form of interviews and observations conducted aims to describe the role of guidance and counseling services in the field of career development in preparing students to face the F phase in the independent curriculum, especially in the context of transition towards higher education. The method used is descriptive qualitative with data collection techniques through in -depth interviews with BK teachers at SMA Negeri 2 Palembayan. The results showed that career development services were carried out systematically through the assessment of interest and talent, providing career information, individual counseling, and the use of information technology. The achievements of students who passed the national selection path based on achievement (SNBP) experienced a significant increase, from 5% in the school year 2023/2024 to 36% in the school year 2024/2025. This shows that BK services that are designed adaptively and focused can increase student readiness in making career decisions. Thus, career development services play an important role in supporting the academic success and future planning of students.